(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Hong Kong's crowded city, with its old buildings and many people, has some tough structural and fire safety problems. In 2024, a significant incident happened when an illegal structure fell down at Redhill Peninsula on Hong Kong Island. Luckily, nobody died, but a lot of property was damaged. Then, in 2025, a terrible fire in Tai Po killed 176 people and got everyone worried again about how safe buildings are from fires. These two significant events were a wake-up call, showing some large weaknesses in how buildings are kept up, problems with illegal construction, and issues with fire safety equipment. This paper looks at the different things that cause buildings to fail and fires to happen in Hong Kong. This includes old buildings, changes to structures that were not allowed, badly designed drainage, and poor upkeep of fire equipment, and bad renovation work. The paper also looks at what the Hong Kong Government has done to fix these problems, like the Minor Works Control System, the Mandatory Building Inspection Scheme, and new rules from the Fire Services Department. It talks about how important Registered Inspectors and Registered Professional Engineers are when it comes to making these safety measures work. It also discusses about good inspection methods, paperwork, and doing a good job as a professional. By looking at all this, the hope is to add something to the talks about safety and stopping disasters in cities with lots of people.